Effect of gradual temperature increase on the carbohydrate energy metabolism responses of the Antarctic fish Notothenia rossii. (September 2019) - Guillen, Angela Carolina; Borges, Marcelo Eduardo; Herrerias, Tatiana; Kandalski, Priscila Krebsbach; de Arruda Marins, Elen; Viana, Douglas; de Souza, Maria Rosa Dmengeon Pedreiro; Oliveira do Carmo Daloski, Letícia; Donatti, Lucélia
Abstract: The warming of the Southern Ocean waters may affect the biological processes and the performance of the fish inhabiting it. The notothenioid group is metabolically specialized to low-temperature environments and may be vulnerable to the climatic changes imposed on the Antarctic continent. However, gradual temperature changes potentially allow an opportunity for plasticity adjustments. The present study evaluated the effect of gradual increase of temperature on the enzymatic and nonenzymatic parameters of energy metabolism in renal, branchial, hepatic, and encephalic tissue of Notothenia rossii subjected to a gradual temperature change of 0.5 °C/day until reaching 2 °C, 4 °C, 6 °C, and 8 °C. Under the effect of an acclimation rate of 0.5 °C/day, the gill tissue showed increased phosphofructokinase (PFK) enzyme activity. In the kidney, there was increased activity of the malate dehydrogenase (MDH), glucose-6-phosphatase (G6PDH), and glycogen phosphorylase (GP) enzymes. There was an increase in lactate concentration in the liver and an increase in GP enzyme activity in the brain. The specific tissue responses indicate the presence of thermal plasticity and an attempt to regulate energy metabolism to mitigate thermal stress in this species under these experimental conditions, possibly through the activation of glycolysis, gluconeogenesis, and glycogenolysis. Highlights: Gradual acclimation trigger different metabolic responses in different organs. Responses of gradual temperature increase are different from those of acute stress. Nothotenia rossii has plasticity and phenotypic abilities to tolerate changes. Kidneys, liver and brain were able to reestablish the energy balance. There was a persistent activation of the glycolysis process in gills.